2009
DOI: 10.1088/0741-3335/51/7/075006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical experiments on plasma focus neutron yield versus pressure compared with laboratory experiments

Abstract: Published literature shows that the neutron yield of the plasma focus has been modeled in two papers using a thermonuclear mechanism. However, it is more widely held that plasma focus neutrons are produced mainly by nonthermalized mechanisms such as beam-target. Moreover these papers use several parameters which are adjusted for each machine until the computed neutron yield Y n data agree with measured Y n data. For this paper numerical experiments are carried out, using the Lee model code, incorporating a bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…The dimension of the CR-39 detectors used are 3.0 9 3.0 cm 2 for 0°and 4.5 9 3.0 cm 2 for 45°, while L M for the mask was 0.8 cm (square), so the FOVs in the source plane were 6.8 9 6.8 cm 2 for 0°and 4.5 9 2.4 cm 2 for 45°. Based on numerical simulations of PF dynamics, the expected dimensions of the PF pinch column are about 10 mm length and 2 mm diameter [11], which are easily within the fully coded FOV. The resolution of a CAI camera is effectively the magnified pixel size in the source plane.…”
Section: Methodsmentioning
confidence: 99%
“…The dimension of the CR-39 detectors used are 3.0 9 3.0 cm 2 for 0°and 4.5 9 3.0 cm 2 for 45°, while L M for the mask was 0.8 cm (square), so the FOVs in the source plane were 6.8 9 6.8 cm 2 for 0°and 4.5 9 2.4 cm 2 for 45°. Based on numerical simulations of PF dynamics, the expected dimensions of the PF pinch column are about 10 mm length and 2 mm diameter [11], which are easily within the fully coded FOV. The resolution of a CAI camera is effectively the magnified pixel size in the source plane.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature and number densities are computed during this phase using shock-jump equations. A communication delay between shock front and current sheath due to the finite small disturbance speed [6,26,39] is crucially implemented in this phase. The model parameters, radial phase mass swept-up and current factors f mr and f cr are incorporated in all three radial phases.…”
Section: As Follows: a Axial Phase (See Figure 1 Left Part)mentioning
confidence: 99%
“…The experimental data ofcurrent curve at 28 kV and 6.6 Torrfor the PF400 is taken from the work by Lee et al [2009]. As usual we first fit the current wave form, for finding the model parameters fm, fc, fmr and fcras discussed in the case of PF1000.…”
Section: Pf400mentioning
confidence: 99%
“…As usual we first fit the current wave form, for finding the model parameters fm, fc, fmr and fcras discussed in the case of PF1000. To obtain the reasonably good fit the following bank and tube parameters (L 0 , C 0 and z 0 refitted and r 0 fitted) are used: The computed current waveform fitted to the measured current waveform [Lee et al 2009] is shown in Figure 2. The fit is good up to the end of the radial pinch phase.…”
Section: Pf400mentioning
confidence: 99%